Advanced Nanofiber-Based Scaffolds for Achilles Tendon Regenerative Engineering - Zhu, Senbo; He, Zeju; Ji, Lichen; Zhang, Wei; Tong, Yu; Luo, Junchao; Zhang, Yin; Li, Yong; Meng, Xiang; Bi, Qing (Frontiers in Bioengineering and Biotechnology, 2022)
The Achilles tendon (AT) is responsible for running, jumping, and standing. The AT injuries are very common in the population. In the adult population (21–60 years), the incidence of AT injuries is approximately 2.35 per 1,000 people. It negatively impacts people’s quality of life and increases the medical burden. Due to its low cellularity and vascular deficiency, AT has a poor healing ability. Therefore, AT injury healing has attracted a lot of attention from researchers. Current AT injury treatment options cannot effectively restore the mechanical structure and function of AT, which promotes the development of AT regenerative tissue engineering. Various nanofiber-based scaffolds are currently being explored due to their structural similarity to natural tendon and their ability to promote tissue regeneration. This review discusses current methods of AT regeneration, recent advances in the fabrication and enhancement of nanofiber-based scaffolds, and the development and use of multiscale nanofiber-based scaffolds for AT regeneration.